MELAMPAUI TAFSIR POSITIVISME HUKUM DALAM PERADILAN ASRORI - Faisal . (Qistie Jurnal Ilmu Hukum, 2011)
Growth of positivism can not be separated from the paradigm of Rene Descartesand Isac Newton, who is often referred to as the Cartesian-Newtonian. Cartesian-Newtonian paradigm is, one side managed to develop science and technologiesthat facilitate human life, but on the other hand reduce the complexity andrichness of human life itself. Cartesian-Newtonian paradigm to treat human andsocial system like a big machine that is set according to the conceptual basis ofobjectivism, determinism, reductionism, materialism-saintisisme,instrumentalisme, dualism and the mechanistic. This was the cause of theCartesian-Newtonian paradigm stands firmly in inspiring understand positivism,and gradually also affect the science of law.Keywords: Legal Positivism, the Revolution of Science, Law Progressive